Preparation of hydroxyapatite hydrogel for bone-like materials via novel self-initiated photocatalytic polymerization - Apichart Han (2018)
© 2017 Elsevier B.V. Here, a novel polyacrylamide (PAM)/hydroxyapatite (HA) composite hydrogel was prepared by the self-initiation of hydroxyapatite via its photocatalytic activity. The radical used as the initiator was produced during irradiation and can initiate the formation of the well-distributed HA in the PAM/HA composite. The in vitro bioactivity in SBF of the novel self-initiated PAM/HA(Ti) hydrogel was faster and better than the conventionally synthesized polyacrylamide hydrogel. The faster formation and larger amount of new apatite in SBF can be observed in the SEM images.